A Proposal of Remedies for Oral Diseases Caused by Candida: A Mini Review - Ohshima, Tomoko; Ikawa, Satoshi; Kitano, Katsuhisa; Maeda, Nobuko (Frontiers in Microbiology, 2018)
An opportunistic pathogen, Candida is not only related to oral problems such as oral candidiasis and denture stomatitis, but also to systemic diseases such as aspiration pneumonia and fungemia. The carriage rate of Candida species in the oral cavity of individuals wearing dentures and with removable orthodontic appliances, has increased. Moreover, it is one of the causal pathogens in refractory infected root canals because of its resistance to antifungal drugs in root canal therapy and poses a great challenge during the treatment of patients. This problem has led to the search for alternative strategies for the treatment and management of C. albicans infections. In this mini review, recent preventive strategies against Candida infection in the oral mucosa with natural product-derived antifungal molecules were discussed. Inhibitory strategies by introducing competitive naturally-derived antifungal peptide molecules with Candida adhesion molecules were specifically introduced. In addition, novel sterilization methods for Candida-infected root canals and tooth structures in the oral cavity were considered, with focused attention on the activities of reactive oxygen species. The possibility of application of these novel strategies in clinical treatments and daily life was also proposed.